2017
DOI: 10.1055/s-0042-123502
|View full text |Cite
|
Sign up to set email alerts
|

Systematischer Review von Übersichtsarbeiten zu Interventionen der Bewegungsförderung: Methodologie und erste Ergebnisse

Abstract: As part of the development of recommendations for physical activity promotion, a review of reviews was performed. This article presents both the utilised methodology and first results.A systematic review of reviews was performed in PubMed, Scopus, Sport Discus, PsycInfo and other electronic databases. Reviews in English and German were included.213 reviews were identified for further analysis. A large number of reviews were identified for physical activity promotion among children and adolescents (74) and adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…1 The methodology used for the systematic review of reviews is briefly described below. A more detailed characterisation has already been explicated [29, 30].…”
Section: Methodsmentioning
confidence: 99%
“…1 The methodology used for the systematic review of reviews is briefly described below. A more detailed characterisation has already been explicated [29, 30].…”
Section: Methodsmentioning
confidence: 99%
“…The recommendations for PA promotion resulted from three comprehensive literature reviews on the topics of efficacy/effectiveness of PA interventions [38], cost-effectiveness of PA interventions [39, 40] and quality criteria for their implementation [41]. Early on, it was decided that the main goal was to establish a firm evidence base for PA promotion in order to ensure political impact.…”
Section: Main Textmentioning
confidence: 99%
“…In order to answer these questions, the following reviews were conducted:Systematic review of reviews on the efficacy and effectiveness of interventions [38], which ultimately identified 213 reviews that dealt with the topic of PA promotion. Six electronic databases were searched in the process.…”
Section: Main Textmentioning
confidence: 99%
“…To integrate practice-based evidence with scientific evidence, the next step included a comparison of these key components with the recent evidence from the literature regarding the effectiveness of community-based PA-promotion focusing on populations with social disadvantages ( Ball et al , 2015 ; Conn and Coon Sells, 2016 ; Mendoza-Vasconez et al , 2016 ; Rütten and Pfeifer, 2016 ; Abu-Omar et al. , 2017 ; Craike et al , 2018 ; Griffith et al , 2018 ; Hu et al , 2019 ).…”
Section: Resultsmentioning
confidence: 99%